Dialektics of Bicultural Identity in Intercultural Communication: A Phenomenological Study Approach - Halimatusa’diah HALIMATUSA'DIAH (Indonesia Strategic Sustainability, 2023)
This study aims to understand and analyze the ways in which bicultural individuals identify as Betawi people in building meaning about their identity in situations of intercultural communication. This study uses a qualitative approach that in its implementation uses a type of understanding. The subjects of the study were bicultural individuals in Jakarta who identified themselves as Betawi people. This study concludes that, first, the meaning of identity to be a Betawi Person is implemented by bicultural individuals by internalizing Betawi cultural values in their daily lives. Local wisdom